Cemented carbide, blades and knives made from them
Patent Information
- Application Number
- JP2021162738
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-01
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-10-01
AI Technical Summary
【0008】 この発明による超硬合金は,平均粒径が1.5μm以下であるWCを主成分とする硬質相を超硬合金全体に対して61~83wt%含み,Niを主成分とする結合相を超硬合金全体に対して16~34wt%含み,Crを主成分とする粒成長抑制相を超硬合金全体に対して1~5wt%含み,硬質相と結合相と粒成長抑制相との合計が100wt%であり,上記WC同士の結晶粒界にNiが含まれており,さらに以下の(1)または(2)の少なくともいずれか一つを備えていることを特徴とする。 (1)上記WC結晶粒子同士の粒界にCrが含まれている。 (2)上記WC結晶粒子と上記Niの粒界にCrが含まれている。
Smart Images

Figure 0007644694000002 
Figure 0007644694000003 
Figure 0007644694000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a cemented carbide, particularly a cemented carbide suitable for cutlery. The present invention also relates to a cutlery and a kitchen knife made using the above-mentioned cemented carbide. [Background technology]
[0002] Important characteristics of blades, such as knives, are their sharpness and durability. Sharpness of a knife can be improved by forming the edge at a sharp angle. However, if the angle is too sharp, the edge is more likely to chip. Furthermore, as the knife is used, the edge wears down and its sharpness decreases. Sustained sharpness (durability) is also essential. Furthermore, because knives are used to cut food, they need to be resistant to corrosion (corrosion resistance).
[0003] There is a demand for materials suitable for cutting tools such as kitchen knives that are excellent in sharpness, durability, and corrosion resistance. Patent Document 1 discloses a cemented carbide containing tungsten carbide (WC), nickel (Ni), and chromium (Cr) that has excellent mechanical strength, corrosion resistance, and polishing gloss. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 64-8245 Summary of the Invention [Problem to be solved by the invention]
[0005] The object of the present invention is to provide a cemented carbide alloy which, when processed into a blade, is resistant to loss of sharpness, i.e., can be used to produce a blade with excellent durability.
[0006] Another object of the present invention is to provide a blade whose sharpness is resistant to deterioration, i.e., which has excellent durability.
[0007] Another object of the present invention is to provide a knife whose sharpness is resistant to deterioration and which cuts comfortably. [Means for solving the problem]
[0008] The cemented carbide of the present invention is characterized in that it contains 61 to 83 wt% of a hard phase mainly composed of WC having an average grain size of 1.5 μm or less, 16 to 34 wt% of a binder phase mainly composed of Ni, and 1 to 5 wt% of a grain growth inhibitor phase mainly composed of Cr, the total of the hard phase, binder phase, and grain growth inhibitor phase being 100 wt%, Ni is contained in the crystal grain boundaries between the above-mentioned WC, and further has at least one of the following (1) or (2). (1) Cr is contained in the grain boundaries between the above-mentioned WC crystal grains. (2) Cr is contained in the grain boundaries between the WC crystal grains and the Ni grains.
[0009] Inevitable impurities, that is, impurities that are present in raw materials or that are inevitably mixed in during the manufacturing process and that are essentially unnecessary but are tolerated because they are present in trace amounts and do not affect the characteristics of the product, may be contained in the cemented carbide of this invention.
[0010] The cemented carbide of this invention contains three types of phases: a "hard phase", a "binding phase", and a "grain growth inhibitor phase". The total of these three phases is 100%. The content of these phases is analyzed using an energy dispersive X-ray fluorescence analyzer.
[0011] The hard phase is mainly composed of tungsten carbide (WC). WC is fine, and nickel (Ni) is used as a binder phase to bind the fine WC. Cemented carbide contains many WC (WC crystal grains), and many WC crystal grains are bound to each other by Ni. In addition to WC and Ni, the cemented carbide of the present invention contains chromium (Cr) (Cr or chromium carbide (Cr 3 C 2 ) is contained in cemented carbide. Cr or Cr 3 C 2can effectively suppress the grain growth of WC during sintering, which allows fine grain WC to be contained in the cemented carbide. 3 C 2 It also provides oxidation resistance to the cemented carbide, making it possible to obtain cemented carbide with excellent corrosion resistance. However, since Cr dissolves in Ni, it is possible to obtain a mixture of Ni and Cr or Cr 3 C 2 In cemented carbide, the above cannot be distinguished from each other visually.
[0012] The cemented carbide according to the present invention is characterized in that either (1) or (2) below is observed at the grain boundaries of WC crystal grains.
[0013] (1) Cr is contained in the grain boundaries between the WC crystal grains. (2) Cr is contained in the grain boundaries between the WC crystal grains and the Ni grains.
[0014] Elements present at the grain boundaries between WC crystal grains and at the grain boundaries (interfaces) between WC crystal grains and Ni can be detected by line analysis using an energy dispersive X-ray spectrometer (EDS).
[0015] Cr may or may not be present at the grain boundaries between WC crystal grains. The same is true for the grain boundaries between WC crystal grains and Ni; Cr may or may not be present at the grain boundaries between WC crystal grains and Ni.
[0016] One of the methods to make Cr exist at the grain boundaries between WC crystal grains and between WC crystal grains and Ni is to change the sintering temperature when sintering the cemented carbide. By setting the sintering temperature in the low range, it is possible to make Cr exist at the grain boundaries between WC crystal grains and between WC crystal grains and Ni. Conversely, if the sintering temperature is set in the high range, it becomes difficult for Cr to exist at these grain boundaries.
[0017] It was confirmed that a cemented carbide containing Cr in the grain boundaries between the WC crystal particles and Cr in the grain boundaries between the WC crystal particles and the Ni has a large difference in durability (resistance to deterioration of sharpness), one of the characteristics required for a blade, compared to a cemented carbide that does not contain these, even if the composition is the same. The cemented carbide provided by this invention is hard and has excellent durability, making it suitable as a material for blades. As mentioned above, it also has excellent corrosion resistance, making it particularly suitable as a material for kitchen knives.
[0018] The present invention also provides a blade having at least a blade portion formed of the above-mentioned cemented carbide. The blade includes a kitchen knife, scissors, a sickle, an axe, a knife, a carving knife, etc.
[0019] The present invention also provides a kitchen knife made from the above-mentioned cemented carbide, in which the opening angle of the cutter blade (cutter blade angle) is 25 to 40°, the opening angle of the relief portion (relief angle) is 2 to 6°, and the boundary between the cutter blade and the relief portion is chamfered. This provides a kitchen knife that is comfortable to cut with and easy to use. [Brief description of the drawings]
[0020] [Figure 1] FIG. [Diagram 2] 1 is a flowchart showing a method for manufacturing a cemented carbide and a kitchen knife. [Diagram 3] This is an electron microscope photograph of a cemented carbide alloy. [Figure 4] 1 is a photograph showing the results of line analysis of a cemented carbide alloy using an energy dispersive X-ray spectrometer. [Diagram 5] 1 is a graph showing the relationship between the flexural strength of a cemented carbide alloy and the amount of loss in sharpness of a knife made from the cemented carbide alloy. [Figure 6] 1 is a graph showing the relationship between the hardness of a cemented carbide alloy and the amount of deterioration in the sharpness of a knife made from the cemented carbide alloy. [Figure 7] FIG. [Figure 8] (A) shows a schematic of a vertical model of the blade, and (B) shows a schematic of an inclined model of the blade. [Figure 9] 13 is a graph showing the relationship between the cutting edge angle and the tensile stress applied to the cutting edge for the vertical model and the inclined model. [Figure 10] 1 is a graph showing the relationship between the cutting edge angle and the stress applied to the object for both the vertical model and the inclined model. [Figure 11] This is a graph showing the relationship between the cutting edge angle and the force required to push the blade in for both the vertical model and the inclined model. [Figure 12] The test results are shown for cutting test paper using four different blades with cutter angles of 30°, 40°, 60°, and 90°. [Figure 13] 13 is a graph showing the relationship between the indentation amount and the indentation load when the relief angle is 2°, 4°, and 6°. [Figure 14] 1 is a graph showing the relationship between the indentation amount and the indentation load for a blade with a chamfered boundary between the cutting edge and the relief portion (with chamfer) and a blade without a chamfered boundary (without chamfer). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] (Basic knife shape and sharpness testing) Figure 1 shows a knife and the knife's performance (sharpness) being tested.
[0022] The knife 1 has at least a blade 2 made of cemented carbide, which will be described later. The blade 2 has a back portion 3 that extends in a straight line and an arc-shaped blade portion 4 on the opposite side, and the blade portion 4 gradually approaches the back portion 3 as it approaches the cutting tip, where it continues with the back portion 3. The tip (cutting edge) of the blade portion 4 is sharp, and foodstuffs are cut by pressing the blade portion 4 against them (and moving it back and forth).
[0023] The sharpness of knife 1 decreases the more knife 1 is used. Knife 1 with blade 2 made of cemented carbide is no exception, but compared to conventional knives made of steel, ceramics, stainless steel, and other materials, knives made of cemented carbide are much less likely to lose their sharpness (they are more durable).
[0024] In this embodiment, the sharpness and durability of the knife 1 are evaluated by preparing a stack of multiple sheets of paper 7, applying a predetermined load to the blade 2 of the knife 1 and pressing it against the stack of paper 7, and then moving the knife 1 a predetermined distance to measure the length (cutting depth) that the stack of paper 7 can be cut through. A knife 1 with good sharpness cuts a long length (cutting depth) of the stack of paper 7, and as the sharpness of the knife decreases, the cutting length becomes shorter.
[0025] (About cemented carbide) The cemented carbide that constitutes the blade 2 of the knife 1 is composed of a hard phase mainly composed of tungsten carbide (WC), a binder phase mainly composed of nickel (Ni), and chromium (Cr) or chromium carbide (Cr 3 C 2 It is a so-called tungsten carbide-based cemented carbide that contains a grain growth inhibiting phase mainly composed of tungsten carbide.
[0026] (1) WC (hard phase) content The hardness of the cemented carbide is based on the hard phase. The cemented carbide of this embodiment contains hard and fine WC as a hard phase. If the WC content is less than 61 wt% of the entire cemented carbide, the binder phase (Ni) becomes relatively more, and the hardness of the cemented carbide decreases. The WC content is set to 61 wt% or more of the entire cemented carbide. According to the performance test described later, it is preferable that it is 66 wt% or more. On the other hand, if the amount of WC is too large, the flexural strength of the cemented carbide decreases and it lacks impact resistance (it is easy to chip). From this point of view, the WC content is set to 83 wt% or less of the entire cemented carbide. According to the performance test described later, it is preferable that it is 78 wt% or less. Furthermore, if the average grain size of WC is large, the hardness of the cemented carbide decreases, so the average grain size of WC is set to 1.5 μm or less. According to the performance test described later, it is preferable that it is 0.2 to 1.0 μm.
[0027] (2) Ni (binder phase) content The binder phase is used to bond the hard and fine WC crystal particles together.
[0028] The cemented carbide of this embodiment contains Ni as a binder phase. The binder phase may be a metal containing Ni as a main component (containing 50 wt% or more of Ni with respect to the entire binder phase).
[0029] If the binder phase is less than 16 wt% of the entire cemented carbide, the flexural strength of the cemented carbide decreases, and if it exceeds 34 wt%, the hardness of the cemented carbide decreases. From these points of view, the binder phase is set to 16 to 34 wt% of the entire cemented carbide. According to the performance test described later, it is preferable that the binder phase be 20 to 30 wt%. By firmly binding the WC crystal particles together with the binder phase, the WC crystal particles are prevented from falling off the cemented carbide, and the strength of the cemented carbide can be ensured.
[0030] (3)Cr or Cr 3 C 2 Content of Cr or Cr 3 C 2 It is used to suppress the grain growth of the WC phase. It is also known that Cr contributes to improving the strength of the binder phase and the oxidation resistance of the cemented carbide. Cr or Cr 3 C 2 When the content of 1.0 wt% or more of WC in the entire cemented carbide is high, the grain growth of the WC phase is suppressed, the strength and oxidation resistance of the binder phase are improved, and the hardness and strength of the cemented carbide are improved. 3 C 2 In order to fully dissolve Cr or Cr 3 C 2 According to the performance test described later, it is preferable that the content is 2.4 to 4.0 wt%.
[0031] (About the manufacturing method of cemented carbide and kitchen knives) FIG. 2 is a flow chart showing a method for manufacturing the cemented carbide and the kitchen knife 1.
[0032] As the raw material powder, WC11 with an average particle size of 0.05 to 2.0 μm was weighed out so that it would be 61 to 83 wt% of the cemented carbide to be produced, and as the binder phase, a metal mainly composed of Ni12 was weighed out so that it would be 16 to 34 wt% of the cemented carbide, and Cr 3C 2 The raw powder 13 is weighed out so that the total amount is 100 wt%. Tungsten powder 14 or carbon powder 15 may be added to the raw powder so that free carbon or decarburized phases are not generated after sintering. These are put into an attritor or ball mill together with an organic solvent and mixed (step 21).
[0033] The attritor is equipped with a cylindrical container and a bladed shaft, and the above-mentioned raw material powder, numerous small-diameter balls made of cemented carbide, and an organic solvent such as acetone, alcohol, or hexane are placed in the cylindrical container. The raw material powder is crushed and mixed in the container by rotating the bladed shaft. The organic solvent enhances the crushing effect and prevents the oxidation of the powder. In this way, a slurry (mud-like material) is obtained.
[0034] A ball mill is equipped with a cylindrical container in which the above-mentioned raw material powder, numerous small-diameter balls made of cemented carbide, and an organic solvent such as acetone, alcohol, or hexane are placed. The raw material powder is crushed and mixed inside the cylindrical container by rotating it. As described above, the organic solvent enhances the crushing effect and prevents the powder from oxidizing. In this way, a slurry is obtained.
[0035] The resulting slurry is then dried using a spray dryer method, a mixer drying method, or the like, thereby removing the organic solvent from the raw material powder (step 22).
[0036] The raw powder from which the organic solvent has been removed is pressed and compacted by die molding, rubber molding, extrusion molding, etc., and molded into the desired shape (step 23).
[0037] The molded product is sintered in a vacuum furnace at a temperature above the ternary eutectic temperature of W-Ni-C (tungsten-nickel-carbon), for example 1380°C, to produce a cemented carbide with WC as the hard phase and Ni as the binder phase (step 24).
[0038] The sintering temperature of 1380°C mentioned above is slightly lower than the general sintering temperature (approximately 1400°C) when manufacturing cemented carbide. By controlling the sintering temperature to the low temperature side, as described below, it is possible to control the state of the grain boundaries of the WC crystal particles, and this makes it possible to manufacture a cemented carbide suitable for the blade 2 of the knife 1. Details of the cemented carbide suitable for the blade 2 of the knife 1 will be described later.
[0039] Finally, the blade 2 of the knife 1 made of cemented carbide is manufactured by shaping. Specifically, the rough shape of the blade 2 is cut out using a wire electric discharge machine, and then it is ground to the desired thickness using a surface grinding machine. Finally, the blade 4 is formed by grinding using a blade grinding machine.
[0040] (Observation results and blade performance tests) Table 1 shows the results of the blade performance test of knife 1, and shows the composition (content of each component) of the cemented carbide alloy that makes up 13 types of knife 1 (Examples 1 to 6, Comparative Examples 1 to 7), measured values and grain boundary observation results, along with the blade performance test results.
[0041] [Table 1]
[0042] Of Examples 1 to 6 and Comparative Examples 1 to 7, the cemented carbide of Examples 1 to 6, Comparative Examples 1 to 5, and Comparative Example 7 was sintered at a sintering temperature of 1380°C. Only the cemented carbide of Comparative Example 6 was sintered at a relatively high sintering temperature of 1400°C.
[0043] The "composition" (content of each component in the cemented carbide) was analyzed using an energy dispersive X-ray spectroscopy (X-ray fluorescence) analyzer.
[0044] "WC grain size" was measured using a scanning electron microscope to observe the polished surface of the sintered cemented carbide alloy and the intercept method. "Hardness" was measured using a Rockwell hardness tester (A scale). "Transverse rupture strength" was measured by a three-point bending test. "Izod impact value" was measured using an Izod impact tester. WC grain size, hardness, transverse rupture strength and Izod impact value are all average values obtained by averaging multiple measured values.
[0045] The "grain boundary observation results" indicate (1) whether Cr exists at the grain boundary between WC crystal particles (Cr between WC-WC), (2) whether Cr exists at the grain boundary between WC crystal particles and Ni (Cr between WC-Ni), and (3) whether Ni exists at the grain boundary between WC crystal particles (Ni between WC-WC), with "present" indicating presence and "absent" indicating absence, respectively. The grain boundaries between WC crystal particles and the grain boundaries between WC crystal particles and Ni were identified by observation with a transmission electron microscope (TEM), and the presence or absence of Cr and Ni at the grain boundaries was identified by line analysis using an energy dispersive X-ray spectrometer (EDS) near the identified grain boundaries. In this example, if the presence of Cr and Ni was confirmed in at least three grain boundaries selected from an arbitrary TEM analysis field of view of 10 μm square, it was determined to be "present."
[0046] FIG. 3 is a cross-sectional photograph (dark field image) of the cemented carbide shown in Example 2 of Table 1, taken using a transmission electron microscope. FIG. 4 shows the results of line analysis of the cemented carbide shown in Example 2 using an energy dispersive X-ray spectrometer. Referring to the cross-sectional photograph in FIG. 3, it can be seen that the cemented carbide of Example 2 contains many WC crystal particles with relatively sharp corners. In the line analysis results in FIG. 4, elements present at the grain boundaries between WC crystal particles are clearly indicated by color coding such as red, blue, yellow, etc. Elements present at the grain boundaries between WC crystal particles and Ni are similarly displayed by color coding. Please note that in FIG. 4, the color coding such as red, blue, yellow, etc. is expressed only by brightness (density).
[0047] The results of the blade performance test show the cutting edge angle (minor blade angle), sharpness, durability and notes of Knife 1.
[0048] The "edge angle" is the cross-sectional angle (opening angle) of the tip (small blade) of the blade 4 of the blade 2, and is standardized at 25° except for Comparative Example 7. "Sharpness" is the cutting length (depth) when a stack of paper 7 (see Figure 1) is cut using a brand new, unused knife 1. "Durability" indicates the degree to which the sharpness is maintained when the total cutting length (depth) reaches 1000 mm. The number of movements of the knife 1 required until the total cutting length reaches 1000 mm is counted, and the value obtained by dividing 1000 by the number of movements is shown in the "Durability" column. The larger the value shown in "Durability", the longer the cutting distance per movement, indicating that the sharpness is less likely to deteriorate even with repeated use. "Notes" shows the observation results of the blade 4. In detail, the load applied to the blade 2 was 8 N, and the movement length of the knife 1 was 10 mm. The stack of paper 7, which is the object to be cut, had a weight of about 43 g / m 2 The paper used had a basis weight equivalent to that of newspaper and was stacked to a height of 7.5 mm. The blade 4 was placed perpendicularly against the paper stack 7.
[0049] The knife 1 of Comparative Example 7 has a cutting edge angle (small blade angle, opening angle of the small blade portion, described later) of 40°, and has poor sharpness (0.8 mm). The knives 1 of Examples 1 to 6 and Comparative Examples 1 to 6, which have a cutting edge angle of 25°, all had the same sharpness when unused (2.5 mm). A cutting edge angle of about 40° is considered to be inappropriate because it has poor sharpness.
[0050] With reference to "durability," durability, which represents the sharpness of the knife 1 when it is used for a specified period of time (in this example, when it cuts 1000 mm of a stack of paper 7), varies greatly, from 0.3 to 2.2 mm, in each of the examples and comparative examples.
[0051] The cemented carbide used in the knife 1 of Comparative Example 1 has a high WC content (89.0 wt%) and a low Ni content (10 wt%). 3 C 2The content of WC is also relatively low at 1.0 wt%. The cemented carbide used in knife 1 of Comparative Example 2 also has a high WC content (84.0 wt%), a low Ni content (15 wt%), and a high Cr content (1.0 wt%). 3 C 2 The content of Ni is also low (1.0wt%). The knives 1 of Comparative Examples 1 and 2 have low durability (0.3mm and 1.5mm respectively), and the knife 1 of Comparative Example 1 also had large chips. It can be seen that the cemented carbide used in the knives 1 of Comparative Examples 1 and 2 also has low flexural strength and Izod impact value. This is thought to be because although the cemented carbide of Comparative Examples 1 and 2 contains a lot of WC, which is a hard phase, the content of Ni that bonds the WC is too low, so the WC crystal particles cannot be fully held together, resulting in a significant decrease in durability. Considering that a cemented carbide is used for knife 1, the content of Ni as a binding phase needs to be 20wt% or more. Relatively speaking, the WC content needs to be 79wt% or less. Cr or Cr 3 C 2 The content must be at least 1.0 wt%, preferably 2.4 wt% or more.
[0052] The cemented carbide used in the knife 1 of Comparative Example 3 has a low WC content (60.0 wt%) and a high Ni content (35 wt%). 3 C 2 The content of WC is also slightly high (5.0wt%). The cemented carbide used in knife 1 of Comparative Example 4 also has a low content of WC (55.0wt%) and a high content of Ni (40wt%). 3 C 2 The content of WC is also somewhat high (6.0 wt%). It can be seen that the knives 1 of Comparative Examples 3 and 4 also have low durability (1.6 mm and 0.4 mm, respectively) and low hardness. This is thought to be because the cemented carbide alloys of Comparative Examples 3 and 4 have insufficient hardness due to an excessively low content of WC, which is a hard phase, and because the Ni content is relatively high, the cutting edge is plastically deformed, resulting in low durability. Considering that a cemented carbide alloy is to be used for knife 1, the WC content must be at least 61 wt%. Relatively, the Ni content must be 34 wt% or less. Cr or Cr 3 C 2 It is preferable to keep the content at a maximum of 5.0 wt%, preferably 4.0 wt%.
[0053] The cemented carbide used in the knife 1 of Comparative Example 5 has a large WC grain size (1.8 μm). The grain size of the WC raw powder was large, and the grain size did not become smaller even after grinding in an attritor or ball mill. It was confirmed that the cemented carbide of Comparative Example 5 has a slightly low flexural strength and is significantly inferior in durability. It is believed that the large WC grain size causes many WC crystal grains to fall off from the blade portion 4, resulting in low durability. A small WC grain size is essential to maintain durability, and when used in the knife 1, the WC grain size needs to be at most 1.5 μm on average.
[0054] The knife 1 of Comparative Example 6 was considered suitable for use as a knife 1 in terms of the WC content (72.0 wt%), Ni content (25 wt%), and WC grain size (0.4 μm), but the flexural strength and Izod impact value were not very high, and the durability was poor. With reference to the grain boundary observation results, the cemented carbide used for the knife 1 of Comparative Example 6 was one in which no Cr was observed between the WC crystal grains, and no Cr was observed between the WC crystal grains and Ni.
[0055] As described above, the cemented carbide used in knife 1 of Comparative Example 6 was manufactured at a sintering temperature of 1400°C, which is a somewhat high sintering temperature. It is believed that the high sintering temperature resulted in the absence of Cr at the grain boundaries between WC crystal particles, and at the grain boundaries (interfaces) between WC crystal particles and Ni, resulting in a lack of durability when used as knife 1. It is believed that the presence of Cr at the grain boundaries between WC crystal particles, which is controlled by the sintering temperature, and the presence of Cr at the interfaces between WC crystal particles and Ni, affect the transverse rupture strength, Izod impact value, and durability.
[0056] The knives 1 of Examples 1 to 6 have durability in the range of 2.0 to 2.2 mm, are excellent in durability, and maintain their sharpness relatively even after use.
[0057] In Fig. 5, the horizontal axis is the flexural strength of the cemented carbide alloy, and the vertical axis is the value obtained by subtracting "durability" from the above-mentioned "sharpness" (this value is called "decrease in sharpness"), on which the values of the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 7 are plotted. In Fig. 5, the values of Examples 1 to 6 are plotted as circle numbers on a white background, and the values of Comparative Examples 1 to 7 are plotted as circle numbers on a black background.
[0058] In the graph shown in FIG. 5, the cemented carbide used in the knives 1 of Examples 1 to 6 has a flexural strength of 300 kgf / mm 2 On the other hand, the cemented carbide used in the knives 1 of Comparative Examples 1 to 7 has a hardness of 300 kgf / mm 2 From the viewpoint of flexural strength, the flexural strength of the cemented carbide suitable for kitchen knives 1 is 300 kgf / mm 2 More than this is preferred.
[0059] In Fig. 6, the horizontal axis represents the hardness of the cemented carbide, and the vertical axis represents the amount of loss in sharpness, and the values of the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 7 are plotted on the graph. In Fig. 6, the values of Examples 1 to 6 are plotted as circle numbers on a white background, and the values of Comparative Examples 1 to 7 are plotted as circle numbers on a black background.
[0060] In the graph shown in Fig. 6, the hardness of the cemented carbide alloys used in the knives 1 of Examples 1 to 6 is in the range of 81 to 88 HRA. The hardness of the cemented carbide alloys used in the knives 1 of Comparative Examples 1 to 7 is quite low or quite high. From the viewpoint of hardness, the hardness of the cemented carbide alloy suitable for the knife 1 is preferably in the range of 81 to 88 HRA.
[0061] The cemented carbide used in the knife 1 of Comparative Example 1, which caused the chipping, has an Izod impact value of 5.4 kJ / mm 2 The Izod impact value of the cemented carbide used in the kitchen knives 1 of Examples 1 to 6 was 8.0 kJ / mm 2 The Izod impact value of the knife of Comparative Example 2 is 6.5 KJ / mm 2Considering that no major chips occurred in this knife, the Izod impact value needed to prevent chipping of Knife 1 is 7.0 kJ / mm 2 It is considered desirable that this be the case.
[0062] From the graphs in Figures 5 and 6 and the above-mentioned results, it can be seen that the hardness is about 81 HRA or more, and about 300 kgf / mm 2 More than 7.0kJ / mm 2 It is presumed that cemented carbide having the above Izod impact value is suitable for use in the knife 1.
[0063] (Knife shape) FIG. 7 shows an enlarged front view of the blade 2 of the knife 1.
[0064] By using a cemented carbide alloy for the blade 2 of the knife 1, sufficient durability (resistance to chipping) can be maintained even if the thickness T of the blade 2 is reduced to 1 mm or less. The inventors further considered the shape of the blade 2 from the perspective of the cutting comfort when used as the knife 1. Below, we consider shapes suitable for the blade 2 of the knife 1 made of a cemented carbide alloy.
[0065] 7, the blade 2 of the kitchen knife 1 is composed of a blade body 2a, a clearance portion 2b, and a blade portion 2c. In the following description, the opening angle of the blade portion 2c is referred to as a blade angle θ 1 The opening angle of the relief portion 2b is called the relief angle θ 2 It is called.
[0066] The blade 2c of the knife 1 is not always pressed perpendicularly against the object, but is often pressed at an angle. As shown in Figures 8(A) and 8(B), in addition to the vertical model (Figure 8(A)) in which the blade 2c is pressed perpendicularly against the object S, we also analyzed the tilted model (Figure 8(B)) in which the blade 2c is pressed at an angle (angle 10°) against the object S.
[0067] (1) Small blade angle θ 1 Figure 9 shows the tensile stress (dashed line) (vertical axis) applied to the blade 2c of the blade 2 when the blade 2c is placed perpendicularly against the object S and the blade 2 is pressed in by 1 μm (vertical model, Figure 8(A)), and the tensile stress (solid line) (vertical axis) applied to the blade 2c when the blade 2c is placed obliquely against the object S at an inclination angle of 10° and the blade 2 is pressed in by 1 μm (inclined model, Figure 8(B)), as a function of the blade angle θ 1 (See FIG. 7) (horizontal axis) is a variable. From the graph of the tilt model shown by the solid line in FIG. 9, when the cutting edge 2c is placed obliquely against the object S, the cutting edge angle θ 1 When the cutting edge angle θ is less than 25°, 1 The smaller the angle, the greater the tensile stress acting on the blade 2c, and the greater the possibility of chipping the blade 2c. The blade 2c of the knife 1 is not always applied perpendicularly to the object S, but is often applied at an angle, so the inclined model must be considered in addition to the perpendicular model. From the graph in Figure 9, when considering use as a knife 1, 1 It is appropriate to set the angle to 25° or more.
[0068] Figure 10 shows the stress applied to the object S when the blade 2c is pressed against the object S and the blade 2 is pressed in by 1 μm for each of the vertical model (dashed line) and the inclined model (solid line). 1 (See Fig. 7) as a variable. In the vertical model (dashed line), the stress applied to the target object S is 1 The cutting edge angle θ 1 It can be seen that the stress applied to the object S decreases sharply when the angle exceeds 80°.
[0069] Figure 11 shows the force required to press the blade 2c against the target object S and push the blade 2 in by 1 μm for each of the vertical model (dashed line) and the inclined model (solid line). 1 (See Fig. 7) as a variable. In the vertical model (dashed line), the force required for pushing is 1 The cutting edge angle θ 1When the angle exceeds 100°, the force required for pressing increases sharply.
[0070] Figure 12 shows the cutting edge angle θ 1 The test results (sharpness) (cutting length) are shown in the figure, in which a test paper (not shown) was cut using four types of blades 2 with blade angles of 30°, 40°, 60°, and 90°. In this test, the blade 2c was placed perpendicularly against the test paper. 1 When the angle was 60° or 90°, the small blade portion 2c slipped on the test paper, and the test paper could not be cut.
[0071] From the results shown in Figs. 9 to 12, the cutting edge angle θ 1 If the cutting edge angle is less than 25°, chipping is likely to occur. 1 If the cutting edge angle is greater than 40°, the sharpness of the cutting edge will decrease. 1 It is believed that a range of 25 to 40 degrees is appropriate, and that by keeping it in this range a good cutting feel will be achieved.
[0072] (2) Relief angle θ 2 Figure 13 shows the appropriate clearance angle θ 2 (See Fig. 7) This shows the results of a simulation to examine the clearance angle θ 2 The relationship between the indentation amount (mm) (horizontal axis) and the indentation load (N) (vertical axis) when the clearance angle is set to 2°, 4°, and 6° (the small blade angle is standardized to 40°). 2 The smaller the relief angle θ, the smaller the load required for the plunger and the smaller the cutting resistance. 2 should be about 2 to 6 degrees.
[0073] (3) Whether or not the boundary (junction) between the cutting edge and the relief is chamfered Figure 14 shows the relationship between the pushing distance (mm) (horizontal axis) and the pushing load (N) (vertical axis) for a blade 2 (chamfered) (solid line) in which the boundary (joint) between the cutter blade portion 2c and the relief portion 2b has been chamfered (smoothed), and a blade 2 (not chamfered) (dashed line) that has not been chamfered. It can be seen that by chamfering the joint, the initial pushing load when starting to push is smaller, making it easier to push the blade 2 into food. By chamfering the joint, food can be cut smoothly, achieving a comfortable cutting experience. [Explanation of symbols]
[0074] 1. Knife 2 blade 2a Blade body part 2b Relief 2c Small blade part 3 back 4 Blade part 7 stack of paper 11 Tungsten carbide 12 Nickel 13 Chromium carbide
Claims
1. The hard phase mainly composed of WC having an average grain size of 1.5 μm or less is contained in an amount of 61 to 83 wt % based on the entire cemented carbide, The binder phase mainly composed of Ni is contained in an amount of 16 to 34 wt% based on the entire cemented carbide, The carbide alloy contains a grain growth inhibiting phase mainly composed of Cr at 1 to 5 wt % relative to the entire carbide alloy, The total of the hard phase, the binder phase, and the grain growth inhibitor phase is 100 wt %; Ni is contained in the grain boundaries between the WC. A cemented carbide alloy having either (1) or (2) below. (1) Cr is contained in the grain boundaries between the WC grains. (2) Cr is contained in the crystal grains of the WC and in the grain boundaries of the Ni.
2. The device has both (1) and (2) above.
2. The cemented carbide of claim 1.
3. A blade, at least a cutting edge of which is made of the cemented carbide according to claim 1 or 2.
4. A kitchen knife made of the cemented carbide according to claim 1 or 2, The opening angle of the blade is 25 to 40 degrees. The opening angle of the relief portion is 2 to 6 degrees. The boundary between the small blade portion and the relief portion is chamfered. Knife.
Citation Information
Patent Citations
JP1966021202Y1
Kitchen knife made of zirconia ceramic
JP1986159982A
Hard alloy
JP1989008245A
Alloy
US3215510A